Pengaruh Pengaruh School Climate dan Persistence terhadap Citizenship Behavior toward Environment Siswa SMAN Di Jakarta - Kharisma Widarsih (Universitas Negeri Jakarta, 2022)
Environmental problems are very crucial global issues. This problem is caused by irresponsible human activities and only concerned with personal needs without regard to the impact on the environment. One of the efforts that can be made with citizenship behavior toward environment. This research was conducted to determine the effect of school climate and persistence on citizenship behavior toward environment of high school students. This research was conducted at SMAN 68 Jakarta in the odd semester of the 2022/2023 school year with a research sample of 70 students. The method used is a survey method through casual studies and analyzed by path analysis. The result of reliability coefficient calculation of citizenship behavior toward environment was 0,911, persistence was 0,965, school climate was 0,942 which indicates that the instruments can be trusted. The result showed that school climate had a direct effect on persistence significantly, persistence had a direct effect on citizenship behavior toward environment significantly, school climate had a direct effect on citizenship behavior toward environment significantly, and school climate had an indirect effect on citizenship behavior toward environment through persistence significantly. Keywords: Path analysis, school climate, persistence, citizenship behavior toward environment